Modelling population dynamics and seasonal movement to assess and predict the burden of melioidosis - Mahikul, Wiriya; White, Lisa J.; Poovorawan, Kittiyod; Soonthornworasiri, Ngamphol; Sukontamarn, Pataporn; Chanthavilay, Phetsavanh; Medley, Graham F.; Pan-ngum, Wirichada (PLOS Neglected Tropical Diseases, 2019)
Author summary Melioidosis is an infectious disease caused by the Gram-negative bacillus Burkholderia pseudomallei, which exhibits marked seasonality in most settings where it occurs, such as Southeast Asia and Northern Australia. Most of the population at risk of contracting melioidosis lives in rural areas; particularly at risk are those who are exposed to soil and water, such as rice farmers. Thailand’s demography is in a transient phase, with older age groups set to double within a decade. Social impacts of lifestyle changes are reflected in seasonal movement and increasing urbanization. In this study, we used mathematical modelling to examine the impacts of such demographical changes on an important infectious disease and to dynamically predict the disease burden in a developing country setting, namely Thailand. We found that melioidosis incidence was significantly higher among working-age Northeast and transient populations, specifically among males aged ≥45 years old and individuals with diabetes. Improved health education and awareness raising should be implemented on a national scale, with a focus on high-risk groups living in endemic areas, as well as those who move seasonally between these and other areas.